2016
DOI: 10.7863/ultra.15.11021
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of an Aortopulmonary Window With an Interrupted Aortic Arch

Abstract: A prenatal aortopulmonary window with an interrupted aortic arch was detected in a 22-week-old fetus. The 3-vessel and trachea view showed a communication between the ascending aorta and the pulmonary artery. Early postnatal surgery was successful. A PubMed-based search identified all cases of prenatal aortopulmonary windows between 2002 and 2015. Nine articles were identified. The average gestational age at diagnosis was 28 weeks (range, 22-33 weeks). The most frequent aortopulmonary window was type I (40%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…One case met the Berry syndrome criteria. The results were a little different from previous publications, which reported that type I was the most common form, and the most common complication was interrupted aortic arch (5 of 10 [50%]) . The discrepancy may be related to the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…One case met the Berry syndrome criteria. The results were a little different from previous publications, which reported that type I was the most common form, and the most common complication was interrupted aortic arch (5 of 10 [50%]) . The discrepancy may be related to the small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…6 the most common form, and the most common complication was interrupted aortic arch (5 of 10 [50%]). 8 The discrepancy may be related to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, a differential diagnosis with patent ductus arteriosus and common truncus arteriosus can be done by the presence of the signs such as aortic systolic murmur and with signs of left ventricular hypertrophy on electrocardiogram [9,10]. Also, the quality of the peripheral pulse, as well as the loud diastolic murmur, can be used to diagnose APW.…”
Section: Discussionmentioning
confidence: 99%